2017
DOI: 10.1049/iet-bmt.2016.0169
|View full text |Cite
|
Sign up to set email alerts
|

Predictive biometrics: a review and analysis of predicting personal characteristics from biometric data

Abstract: Interest in the exploitation of soft biometrics information has continued to develop over the last decade or so. In comparison with traditional biometrics, which focuses principally on person identification, the idea of soft biometrics processing is to study the utilisation of more general information regarding a system user, which is not necessarily unique. There are increasing indications that this type of data will have great value in providing complementary information for user authentication. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 170 publications
0
7
0
Order By: Relevance
“…Our study can help inform their experimental design. Of our key findings, it is interesting to have identified that the capabilities of a key dynamic system are at their best with no substitution and the password is shorter in length (6). This means that implementing a keystroke biometric system, alongside a strong password policy, might have a negative impact on the biometric system.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Our study can help inform their experimental design. Of our key findings, it is interesting to have identified that the capabilities of a key dynamic system are at their best with no substitution and the password is shorter in length (6). This means that implementing a keystroke biometric system, alongside a strong password policy, might have a negative impact on the biometric system.…”
Section: Discussionmentioning
confidence: 88%
“…Biometric systems provide an alternative approach to authentication whereby physiological, behavioural and chemical characteristics are sensed and used to authenticate a user in replacement (or in addition) to a password. Biometric systems have always been heavily researched, and there is a wealth of literature on the different types and their applications, as presented by these extensive surveys [5,6]. For example, in terms of physiological, fingerprints, and facial features are examples.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, physiological emotion recognition also plays an important role in emotion recognition, which can be inferred from different ways such as biometric [132], [133], EEG signal measurements [134], [135]. As discussed above, these approaches also have the same approaches, such as data collection, pre-processing, and computational intelligence methods, to infer emotions.…”
Section: D: Physiological Emotion Recognitionmentioning
confidence: 99%
“…Studies of the applications of affective biometrics can be found in the literature in the fields of brain biometric analysis [ 15 ], predictive biometrics [ 16 ], keystroke dynamics [ 17 ], applications in education [ 18 ], consumer neuroscience [ 19 ], adaptive biometric systems [ 20 ], emotion recognition from gait analyses [ 21 ], ECG databases [ 22 ], and others. Several works on affective states have integrated multiple biometric and neuroscience methods, but none have included an integrated review of the application of neuroscience and biometrics and an analysis of all of the emotions and affective attitudes in Plutchik’s wheel of emotions.…”
Section: Introductionmentioning
confidence: 99%